2018
DOI: 10.1111/pcn.12784
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide in bipolar disorder: A 30‐day comparison to a retrospective control group treated with other antiepileptics

Abstract: Aim Bipolar disorder (BD) is often treated with anticonvulsants. Lacosamide has not been tested in BD. We assessed its effects in a hospital setting in patients with BD without epilepsy. Methods We treated 102 consecutive hospitalized patients with acute BD with lacosamide 50–300 mg/day. We compared this sample with a retrospective sample treated with other antiepileptics (OAE). We rated patients after 3, 7, 15, and 30 days of treatment with the Brief Psychiatric Rating Scale, Young Mania Rating Scale, Hamilto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Moreover, LCM managed to alleviate the symptoms of depression in the epileptic animals during the post-SE period and to alleviate epilepsy-induced hyperactivity in the activity cage. Data about the effect of LCM on anxiety levels and depression are very scarce, although experimental as well as clinical studies have recently shown improved symptoms after acute or chronic treatment with this drug in rats and epileptic patients [ 47 , 48 , 49 , 50 ], as well as in patients with bipolar disorder without epilepsy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LCM managed to alleviate the symptoms of depression in the epileptic animals during the post-SE period and to alleviate epilepsy-induced hyperactivity in the activity cage. Data about the effect of LCM on anxiety levels and depression are very scarce, although experimental as well as clinical studies have recently shown improved symptoms after acute or chronic treatment with this drug in rats and epileptic patients [ 47 , 48 , 49 , 50 ], as well as in patients with bipolar disorder without epilepsy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with partial-onset seizures, the treatment of epilepsy with lacosamide also may improv anxiety, depression as well as quality of life without worsening indicators of sleep quality and fatigue ( 3 , 73 , 74 ). In addition, lacosamide improved mania, anxiety, depression, and global functioning in the short term when used for the treatment of patients with bipolar disorder compared to other ASMs ( 72 ).…”
Section: Effects Of Lacosamide Treatment On Epilepsy-associated Anxie...mentioning
confidence: 99%
“…Especially, first generation of AEDs may cause a deterioration in cognitive functions thus contributing to a significant reduction in the patient's quality of life [9]. Due to mechanism of action and pharmacokinetic properties, there is an opportunity to use LC not just in epilepsy [10][11][12][13]. It is worth emphasizing, that preliminary preclinical results indicate the possibility of using the drug in Alzheimer's disease [14].…”
Section: Introductionmentioning
confidence: 99%